PAKISTAN’S ROLE IN STABILIZING AFGHANISTAN: STRATEGIES FOR PEACE AND DEVELOPMENT - Sadia Parveen; Israrud Din; Zaiba Sarwar (International Journal of Contemporary Issues in Social Sciences, 2024)
Pakistan’s strategic role in stabilizing Afghanistan through diplomatic engagement, counter-terrorism collaboration, and economic cooperation. It highlights the historical context, current challenges, and potential strategies for fostering peace and progress. The focus is on how Pakistan's multifaceted approach can contribute to lasting stability and regional development. To analyze Pakistan's strategies for contributing to the stabilization and progress of Afghanistan through diplomatic, security, and economic initiatives. This study employs a qualitative approach to analyze Pakistan's role in stabilizing Afghanistan, utilizing secondary sources for comprehensive insights. Pakistan's historical ties and strategic interests in stabilizing Afghanistan are crucial for regional stability and security. Despite challenges, including mistrust and regional dynamics, Pakistan's commitment to the Afghan peace process remains steadfast, emphasizing diplomatic engagement, economic integration, and regional cooperation. Economic integration and development initiatives, such as CPEC and TAPI, are essential for Afghanistan's reconstruction and stability. Pakistan should continue diplomatic engagement with key stakeholders to promote the peace and development in Afghanistan.